Indoor environmental comfort in Malaysian urban housing - Yaik Wah, Lim (Science Publications, 2013)
In Malaysia, terraced houses have been rapidly constructed since 50 years ago and account for 44% of the existing urban housings. However, these houses have very limited use of natural ventilation and daylighting due to openings with small window-to-floor ratio. The deep plan design causes gloomy indoor spaces, low air change rate and poor indoor air quality. Studies showed that indoor environments have major impact on occupants' well-being. Thereby this study evaluates the effects of indoor comforts on occupants' perceived health in Malaysian typical terraced houses. Survey of terraced houses in Johor Bahru, Malaysia was conducted using questionnaire. Various terraced houses were studied to identify the critical comfort and health issues in terraced housing. The relationships among occupants' perceived comforts, health and behavior were studied. The variance of types of terraced house was also analyzed. The findings demonstrated significant linear relationships between indoor comfort and health. However, occupants' behavior did not give significant impact on thermal comfort. This study concludes that it is very essential to improve indoor comfort in Malaysian typical terraced houses through tropical design strategies to enhance occupants' well-being. © 2013 Science Publication.